OPTIMALISASI PENGELOLAAN PELABUHAN-PELABUHAN KUNO DI BULELENG DALAM PENGEMBANGAN PARIWISATA - Ni Komang Ayu Astiti (Forum Arkeologi, 2018)
Buleleng waters had been busy since the 10th century and achieved greatness during the Dutch government. The potential of natural resources and strategic geographical location are the main factors. Political developments led to only three ports that play an active role and as a triangle spot of the Dutch government. The purpose of optimizing management is that the ancient port as a cultural heritage also has an important role and existence in the current development and provide benefits both in the preservation of culture, economic community. This research uses descriptive qualitative approach with field observation data and interview technique. The results obtained that in optimizing the management of ancient ports for tourism development, should be accompanied by connections with subsystems and other tourism support facilities. The harbor and the surrounding landscape can serve as a tourist attraction as well as provide access services to increase the motivation of tourists to learn and gain new knowledge and experience. High tourist motivation to visit Buleleng will directly promote the tourism industry, preservation of ancient ports with various supporting facilities and as a means of diplomacy to become the pride of the people of Buleleng. In optimizing the management of ancient ports in tourism development, it is expected that there will be coordination and synchronization with stakeholders related to the preservation of cultural heritage, environment and tourism industry. Perairan Buleleng sudah ramai sejak abad ke-10 dan mencapai kejayaan pada masa pemerintahan Belanda. Potensi sumber daya alam dan letak geografis yang strategis menjadi faktor utama. Perkembangan politik menyebabkan hanya tiga pelabuhan yang berperan aktif dan sebagai triangle spot pemerintah Belanda. Tujuan optimalisasi pengelolaan adalah agar pelabuhan kuno sebagai warisan budaya juga mempunyai eksistensi dan peran penting dalam pembangunan saat ini serta memberikan manfaat dalam pelestarian budaya. Metode penelitian ini menggunakan pendekatan diskriptif kualitataif dengan teknik pengumpulan data observasi lapangan dan wawancara. Hasil yang diperoleh bahwa dalam melakukan optimalisasi pengelolaan pelabuhanpelabuhan kuno untuk pengembangan pariwisata, harus disertai dengan koneksi dengan subsistem dan fasilitas pendukung pariwisata lainnya. Motivasi wisatawan yang tinggi untuk berkunjung ke Buleleng secara langsung akan memajukan industri pariwisata, pelestarian pelabuhan-pelabuhan kuno dengan berbagai fasilitas pendukungnya dan sebagai sarana diplomasi sehingga menjadi kebanggaan masyarakat Buleleng. Dalam optimalisasi pengelolaan pelabuhan-pelabuhan kuno dalam pengembangan pariwisata diharapkan ada koordinasi dan sinkronisasi dengan stakeholder terkait pelestarian warisan budaya, lingkungan dan industri pariwisata.